Implementasi Konsep “Muni Papua Bageka Tota Kabo Wado Make” pada Interior Museum Negeri Provinsi Papua di Waena, Jayapura - Jessica Andini Gosal; Ronald Hasudungan Irianto Sitindjak; Linggajaya Suryanata (Intra, 2017)
Papua Province State Museum is one of the museums located in Jayapura, Papua which has approximately 3600 collections of art and culture from Papua and West Papua. In fact, this museum is less desirable to visit the public due to the condition of the museum's interior and the presentation of less attractive collections and good maintenance and technical buildings, especially electricity that is unstable so the need for redesain museum for the interior of value and interesting. To achieve this, the redesign of this museum takes the concept of "Muni Papua Bageka Tota Kabo Wado Make" which means caring for a museum based on local culture of Papua so, the design of this museum will feature a warm and comfortable atmosphere that is close to the daily life of the people of Papua in terms of color selection, , Accessories and interior elements at redesain Museum Negeri Provinsi Papua. With this redesign, it is hoped that this museum will become one of the icon of the city of Papua that enhances the image of the city of Papua, enhances the conservation of Papuan culture, adds recreation areas and adds Papuan cultural education.